Agency in language planning and policy. Issue 1 (15th March 2021) - Liddicoat, Anthony J.; Taylor-Leech, Kerry
ABSTRACT: The role of agency in language planning and policy (LPP) is a recent focus of scholarship. Interest in agency has seen new issues and contexts being given prominence in LPP research. In this introduction, we present an overview of theoretical definitions of agency and the ways it has emerged as a concept in LPP scholarship. We consider how developments in methods and approaches to LPP research have led to a greater focus on social actors and their agency in LPP decision-making. We also consider how agency can be conceptualised within the field of language planning, how it may be exercised and who may exercise agency.